Effects of ceramic-based CrN, TiN, and AlCrN interlayers on wear and friction behaviors of AlTiSiN plus TiSiN PVD coatings - Ozkan, Dogus; Yilmaz, M. Alper; Szala, Miroslaw; Turkuz, Cenk; Chocyk, Dariusz; Tunc, Cihan; Goz, Onur; Walczak, Mariusz; Pasierbiewicz, Kamil; Yagci, M. Baris (ELSEVIER SCI LTD, 2021)
In this study, the wear and friction behavior of cathodic arc physical vapor deposited AlTiSiN+TiSiN coatings on H13 tool steels were investigated by using CrN, TiN and AlCrN interlayers with tribometer tests both under unlubricated and boundary lubricated conditions. 6 mm alumina balls were used as counter surfaces to test ceramic hard coatings. Surface coatings were characterized through nanoindentation, scanning electron microscopy coupled with an energy-dispersive X-ray spectrometer (SEM/EDXS), optical profilometry, and atomic force microscopy (AFM) techniques. The results showed that especially AlTiSiN+TiSiN coating with TiN interlayer resulted in a much more enhanced tribological performance of the tool steels at both unlubricated and the boundary lubricated conditions even at elevated contact pressures.
Keywords: Multilayer ceramic coatings; Ceramic interlayers; Boundary lubricating condition; H13 tool steel; Nanoindentation; TRIBOLOGICAL PROPERTIES; CRYSTAL-STRUCTURE; ABRASIVE WEAR; HARD COATINGS; PERFORMANCE; ADHESION; MICROSTRUCTURE; RESISTANCE; THICKNESS; FRACTURE; Materials Science